Proteoglycans synthesized by fetal Guinea pig chondrocytes in culture - Madsen, Kjell; Lohmander, Stefan ; 0000-0002-5424-9448; Moskalewski, Stanislaw; Hinek, Aleksander (Connective Tissue Research, 1978)
Short term cultures were carried out with chondrocytes and tissue fragments from fetal guinea pig epiphyseal cartilage. Proteoglycans were isolated from these cultures and their properties were compared with those of pro-teoglycans from adult hyaline cartilage. It was concluded that the proteoglycans synthesized in culture were essentially similar to those present in cartilage matrix in vivo. The authors therefore suggest that fetal guinea pig chondrocytes cultured in monolayer or as aggregates in suspension constitute a useful system for the study of synthesis and secretion of proteoglycans.